2020
DOI: 10.1111/geb.13205
|View full text |Cite
|
Sign up to set email alerts
|

Global responses of fine root biomass and traits to plant species mixtures in terrestrial ecosystems

Abstract: Aim Fine root traits underpin terrestrial ecosystem functioning. Despite ongoing plant diversity loss due to anthropogenic activities, our understanding of the effects of plant diversity on fine root traits remains elusive. We addressed: (a) Do fine roots modify their traits in response to species mixtures? (b) Do these responses change with the species richness in mixtures, stand age, and soil depth? (c) Do plant‐mixture induced responses of root traits differ across terrestrial ecosystems? Location Global. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
3
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 81 publications
1
22
3
1
Order By: Relevance
“…Yet, our results show underyielding of FRB (Figures 1a and 2a) and no overall changes in RLD (Figures 1b and 2b) across all four forest types. These results contrast with several previous studies in mature (semi‐)natural forests where either a higher FRB in mixtures or no differences across richness levels have been observed (Brassard et al., 2013; Finér et al., 2017; Meinen et al., 2009a; Peng & Chen, 2020).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Yet, our results show underyielding of FRB (Figures 1a and 2a) and no overall changes in RLD (Figures 1b and 2b) across all four forest types. These results contrast with several previous studies in mature (semi‐)natural forests where either a higher FRB in mixtures or no differences across richness levels have been observed (Brassard et al., 2013; Finér et al., 2017; Meinen et al., 2009a; Peng & Chen, 2020).…”
Section: Discussioncontrasting
confidence: 99%
“…Error bars represent one standard error of the mean. Asterisks indicate significant differences between monospecific and mixed stands for the entire soil profile (**p < 0.01, ns p > 0.1) previous studies in mature (semi-)natural forests where either a higher FRB in mixtures or no differences across richness levels have been observed (Brassard et al, 2013;Finér et al, 2017;Meinen et al, 2009a;Peng & Chen, 2020).…”
Section: Mixing Effectsmentioning
confidence: 87%
See 1 more Smart Citation
“…Such biodiversity effects in modern cropping systems are supported by ancient origins and contemporary ecological research [6]. Other experimental and observational studies have advanced our understanding of how such root behavior contributes to the over-yielding that often accompanies biodiversity [4,[7][8][9][10][11]. Some of these studies indicate mechanisms other than nutrient enrichment.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of plant diversity on the vertical distribution of roots has not been as clear, with most of the roots accumulating at the top of the soil (Mommer et al, 2010;de Kroon et al, 2012;Luo et al, 2021). Recently, two meta-analyses showed that increasing plant species richness does not seem to affect the rooting depth of plant communities (Barry et al, 2020;Peng and Chen, 2021). With the exception of one study that reported that high diversity plots in a grassland field experiment had a higher proportion of root biomass allocated to deeper soil layers (Mueller et al, 2013), there is little evidence supporting an increase in vertical root niche differentiation with increased plant diversity in either grasslands (Mommer et al, 2010;Ravenek et al, 2014;Oram et al, 2018) or forests (Valverde-Barrantes et al, 2015;Luo et al, 2021;Zeng et al, 2021).…”
Section: Introductionmentioning
confidence: 99%